The Organizational Internal Environment as an Effective Factor for - Khachian, alic; Houman Manoochehri, Houman; Pazargadie, Mehrnoosh; Akbarzadeh Baghban, Alireza (Advances in Nursing & Midwifery, 2013)
Abstract Background and Aim The internal environment of any organization is an effective factor on change management. There are many effective factors which should be determined and utilized for change management in any organization including nursing and midwifery schools. So, this study aimed to explore organizational internal environment of nursing and midwifery schools and it’s effect on change management. Materials and methods This study was the qualitative part of a mixed exploratory study. The participants were recruited by purposeful sampling method from the managers of Tehran schools of nursing and midwifery. Data were gathered by semi-structured interviews and conventional content analysis was used for data analysis. Findings Totally, 171 conceptual codes were extracted which were categorized in 3 themes including changing process, internal organizational environment and external organizational environment. Internal organizational environment had 10 subcategories in 3 main categories including managerial-, organizational- and individual-factors Conclusion: The concept of change management is a complicate procedure which is influenced by managerial-, organizational- and individual-factors. Faculty members, manager’s duties, education, attitude and other factors should be considered for change management in schools of nursing and midwifery. Keywords: Change management, Change, Nursing school. *Corresponding Author: Alice Khachian, Ph.D student of nursing, School of Nursing & Midwifery, Shahid Beheshti University of Medical Sciences E-mail : dr.houmanmanoochehri@gmail.com -Sange P (2007). A Fifth Discipline Resource: Dance of Change. Translated by Akbari H Soltani M. Tehran. Aryana Industrial & Research Group. (Persian) -Andrew J Cameron H Harris M (2008). All Change? Managers’ experience of organizational change in theory and practice. Journal of Organizational Change Management. 21 (3) 300-314. -Bianco A Schermerhorn J J(2006). Self-regulation, strategic leadership and paradox in organizational change. Journal of Organizational Change Management. 19(4)457-470. -Boswell C Cannon SH (2007). Introduction to Nursing Research: Incorporating Evidence-Based Practice. 2nd edition. Boston, Jones and Bartlett Publisher. -Gatto RP (2000). The Smart Manager’s F.A.Q. guide: A Survival Handbook for Today’s Workplace. San Francisco, Jossey- Bass. -Hsieh H Shannon SE (2005). Three approaches to qualitative content analysis. Qualitative Health Research. 15(9)1277- 88. -Johansson C, Heide M (2008). Speaking of Change: Three Communication Approaches in Studies of Organizational Change. Corporate Communications: An International Journal. 13(3) 288-305. -Kordrostami M Aghakhani E (2006) [Change Management and Organizational Development]. Tehran, Darsi books Publication. (Persian). -LoBiondo–Wood G, Haber J (2002) Nursing Research: Methods, Critical Appraisal and Utilization.6th Edition. USA, Mosby. -McCormick D (2007) Dramaturgical analysis of Organizational Change and Conflict. Journal of Organizational Change Management. 20(5)685-699. -David R (2009). [Strategic Management]. Translated by parsayan A, Aarabi M. Iran cultural Studies (Persian). -Reed J Vakola M (2006). What role can a training needs analysis play in organizational change. Journal of Organizational Change Management. 19 (3) 393-407. - Sadeghi D (2011). Alignment of organizational change strategies and its relationship with increasing organizations’ performance. Procedia Social and Behavioral Sciences 20,1099-1107. -Saka A (2003). Internal Change Agents’ View of the Management of Change Problem. Journal of Organizational Change Management. 16 (5) 480-496. -Salsali M Parvizi S Adib Hajbagheri M(2004). [Qualitative Research Methods]; 1st edition, Tehran Boshra Publications. (Persian). -Streubert Speziale HJ, Carpenter Rinaldi D(2007). Qualitative Research in Nursing, Advancing the Humanistic Imperative. 4 th edition. Philadelphia, Lippincott-Williams &Wilkins. -Van Dijk R Van Dick R (2009).Navigating Organizational Change: Change Leaders, Employee Resistance and Work- Based Identities. Journal of Change Management. 9(2)143-63.